Axial thinking and its role in teaching Arabic (literature and texts) Theoretical study (Journal of the College of Basic Education, 2022)
As a result of the enormous knowledge development that characterized the twentieth century, the need for modern societies to teach thinking skills emerged in resp onse and an urgent need for the requirements and challenges of the times and their manifestations in various aspects of life, what the era witnesses of transformations in the fields of science and knowledge, pushed those in charge of the educational issue to pay attention to developing the thinking skills of learners and making it a major goal for him because modern educational trends call for making the learner the focus of the educational process. In fact, it indicates that most teachers account for the explanation without paying attention to thinking questions and giving the positive role of the learner to practice thinking, which leads to poor achievement, and those who follow the teaching of literary texts subject in our schools clearly notice the negative trend of students towards the literary text that is presented to them, and their stumbling in their understanding and taste, in addition to the prevailing pattern is preservation and indoctrination rather than assimilation, which weakens the spirit of innovation, creativity and taste, and this consequence is a weakness that has accompanied Arab generations over years Long, creating an atmosphere of dissonance between students and the subject studied, then the gap between them widened, and this was represented by the lack of achieving the desired benefit from studying it, as required and planned. Because the goal of achievement for the learner is not the knowledge he/she has, but rather the ways of thinking and its axis for the study materials and educational activities used through experiences allow the learner to be active practicing thinking skills exploring information that leads to the thought that helps him to create meaning, understand the content, issue judgments and arrive at sound decisions, through training. And learning for thinking skills for all levels of study, and enabling them to invest the maximum possible of their creativity and potential in order to create a creative and thinking generation.